Whole-genome sequencing of non-typeable Haemophilus influenzae isolated from a tertiary care hospital in Surabaya, Indonesia - Made Ananda Krisna; Lindawati Alimsardjono; Korrie Salsabila; Naritha Vermasari; Wa Ode Dwi Daningrat; Kuntaman Kuntaman; Odile Barbara Harrison; Martin Christopher James Maiden; Dodi Safari (BMC Infectious Diseases)
Abstract Background Haemophilus influenzae causes life-threatening invasive diseases such as septicaemia and meningitis. Reports on circulating H. influenzae causing invasive disease in lower-middle income settings, including Indonesia, are lacking. This study describes the serotype distributions and whole-genome sequence (WGS) data of H. influenzae isolated from hospitalized patients at Soetomo Hospital, Surabaya, Indonesia. Methods H. influenzae isolates were isolated from blood and pleural fluid specimens and identified using culture-based and molecular methods, followed by serotyping and WGS using RT‒PCR and Illumina MiSeq, respectively. Sequencing reads were assembled, and further analyses were undertaken to determine the genomic content and reconstruct the phylogeny. A second dataset consisting of publicly available H. influenzae genomes was curated to conduct phylogenetic analyses of isolates in this study in the context of globally circulating isolates. Results Ten H. influenzae isolates from hospitalized patients were collected, and septicaemia was the most common diagnosis (n=8). RT‒PCR and WGS were performed to determine whether all the isolates were nontypeable H. influenzae (NTHi). There were four newly identified STs distributed across the two main clusters. A total of 91 out of 126 virulence factor (VF)-related genes in Haemophilus sp. were detected in at least one isolate. Further evaluation incorporating a global collection of H. influenzae genomes confirmed the diverse population structure of NTHi in this study. Conclusion This study showed that all H. influenzae recovered from invasive disease patients were nonvaccine-preventable NTHi isolates. The inclusion of WGS revealed four novel STs and the possession of key VF-associated genes.